1. ## Multiplying with indices

Hi, Can you see where I have gone wrong with this please?

Question: Simplify $\displaystyle (x+x+2x^2)^3$

$\displaystyle (x+x+2x^2)^3$

$\displaystyle =(4x^2)^3$

$\displaystyle =(4)^3\times(x^2)^3$

$\displaystyle =64x^6$

(The book's answer is $\displaystyle 27x^6$)

2. Originally Posted by Meggomumsie
Hi, Can you see where I have gone wrong with this please?

Question: Simplify $\displaystyle (x+x+2x^2)^3$
then it is = $\displaystyle (2x+2x^2)^3$ not $\displaystyle (4x^2)^3$

3. Maybe there's an error on what you want?
I can't get $\displaystyle (x+x+2x^2)^3=27x^6$

Maybe it is $\displaystyle (x*x+2x^2)^3$ ??

4. Dohh!! Thank you

5. Thanks Sentinel4 - I have checked in the book and it is

as you suggested.

$\displaystyle =(x*x+2x^2)^3$

$\displaystyle =(x^2+2x^2)^3$

$\displaystyle =(3x^2)^3$

$\displaystyle =(3*3*3)(x^2)^3$

$\displaystyle =27x^6$

Why didn't I see that?

6. Read the exercises more carefully. You saw what difference makes a + instead of * ??
I make this mistake a lot, try to solve it quick, then i realize i forgot a number, a parentheses etc and back to the beginning of the exercise lol